Variabilidade espacial de atributos do solo e vegetação em sistemas de Integração Lavoura-Pecuária-Floresta - Laurenti, Nicolle (Universidade Federal de São Carlos, 2023)
According to the concept of sustainability, agrosystems in the 21st century must be able to maximize the quantity of high-quality agricultural products and, at the same time, at the same time, conserve the system's natural resources. Within this perspective, the Integrated systems emerge as a sustainable production strategy. What does it say respect to the characteristics of the soil and vegetation of production systems, it is known that they can vary spatially depending on intrinsic and extrinsic factors, and the understanding the variability of soil and plant properties has potential to contribute to increasing productivity and quality, saving inputs, and reduction of environmental impact. In this context, the objective of the present work was to study the spatial variability of soil and vegetation attributes in an Integration area Crop-Livestock-Forest (ILPF) and in an area of Livestock-Forest Integration (IPF) in São Carlos-SP using Precision Agriculture tools. For this, they were evaluated in the study area physical and chemical attributes of the soil (depths 0-0.2 and 0.2-0.4 m), its electrical resistivity (depths 0-0.5, 0-1.0 and 0-2.0 m) and attributes of vegetation (periods of April/2021 and April/2022). Regarding chemical attributes, higher pH values were observed in H2O, pH in CaCl2, potassium, calcium, magnesium, cation exchange capacity and base saturation in the ILPF system. As for the attributes organic matter, phosphorus and sulfate, there were no differences between the two systems productive. For all chemical attributes, with the exception of sulfate, it was noted decreasing values with increasing depth. In turn, there was no difference between the ILPF and IPF systems for the physical attributes sand, clay and silt, with the amount of sand and silt in the soil did not change with increasing depth, within the context of the classes considered in the interpolation process. For clay, On the contrary, it was noted that it increased with increasing depth. Concerning electrical resistivity of the soil, it was noted that it increased with increasing depth, with no significant difference between the two production systems. Finally, also no significant difference was observed between systems for vegetation attributes, concluding that growth in both height, DBH and volume of trees was relatively homogeneous. The results indicated that the techniques geoprocessing allowed storing, making available and integrating data georeferenced soil and plant attributes. And the spatial analysis of these attributes through interpolated maps can provide management tools for managing integrated systems
Spatial variability of soil and vegetation attributes in Crop-Livestock-Forest Integration systems
Keywords: Agricultura de precisão; Interpolação espacial; Sistemas integrados; Sustentabilidade; Precision agriculture; Spatial interpolation; Integrated systems; Sustainability; CIENCIAS AGRARIAS::AGRONOMIA::CIENCIA DO SOLO